2020
DOI: 10.1186/s12933-019-0980-4
|View full text |Cite
|
Sign up to set email alerts
|

Sodium–glucose cotransporter 2 inhibitor Dapagliflozin attenuates diabetic cardiomyopathy

Abstract: Background: Diabetes mellitus type 2 (DM2) is a risk factor for developing heart failure but there is no specific therapy for diabetic heart disease. Sodium glucose transporter 2 inhibitors (SGLT2I) are recently developed diabetic drugs that primarily work on the kidney. Clinical data describing the cardiovascular benefits of SGLT2Is highlight the potential therapeutic benefit of these drugs in the prevention of cardiovascular events and heart failure. However, the underlying mechanism of protection remains un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
125
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(139 citation statements)
references
References 44 publications
11
125
1
2
Order By: Relevance
“…SGLT2 inhibitors were shown to significantly improve diastolic function in the human heart, as confirmed in the myocardium of mice with or without DM and further in HFpEF models ( Habibi et al., 2017 ; Pabel et al., 2018 ; Zhang et al., 2019 ). Substantial evidence has suggested that SGLT2 inhibitors ameliorate worsening cardiac dysfunction by reducing cardiac inflammation and oxidative stress ( Ye et al., 2017 ; Li et al., 2019 ; Arow et al., 2020 ; Byrne et al., 2020 ). Although an increasing number of studies on HFpEF have been conducted ( Anker et al., 2019 ), more in-depth research on SGLT2 inhibitors in HFpEF is expected to be conducted in the future.…”
Section: Discussionmentioning
confidence: 99%
“…SGLT2 inhibitors were shown to significantly improve diastolic function in the human heart, as confirmed in the myocardium of mice with or without DM and further in HFpEF models ( Habibi et al., 2017 ; Pabel et al., 2018 ; Zhang et al., 2019 ). Substantial evidence has suggested that SGLT2 inhibitors ameliorate worsening cardiac dysfunction by reducing cardiac inflammation and oxidative stress ( Ye et al., 2017 ; Li et al., 2019 ; Arow et al., 2020 ; Byrne et al., 2020 ). Although an increasing number of studies on HFpEF have been conducted ( Anker et al., 2019 ), more in-depth research on SGLT2 inhibitors in HFpEF is expected to be conducted in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these commonly-used models of diabetes, e.g. streptozotocin-treatment (STZ) and the db/db genetic mouse model, have previously been combined with angiotensin II or uninephrectomy to mimic and accelerate DbCM or DN, respectively 21 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Dapagliflozin is a selective and inverse inhibitor of type 2 glucose cotransporter (SGLT2) [8]. Dapagliflozin lowers glucose levels both after ingestion and on an empty stomach by reducing renal glucose absorption and as a consequence of its excretion in the urine [8]. However, this medicine does not interfere with the normal production of endogenous glucose in response to hypoglycemia and acts independently of insulin secretion and action.…”
Section: Introductionmentioning
confidence: 99%
“…Urinary glucose excretion induced by dapagliflozin is associated with calorie loss and weight loss [9]. Suppression of the co-transport of glucose and sodium by dapagliflozin may be accompanied by minor urine output and temporary excretion of sodium by urine [8].…”
Section: Introductionmentioning
confidence: 99%